PENGARUH SIFAT FISIK TANAH TERHADAP JAMUR AKAR PUTIH PADA TANAMAN KARET - Ken Shavira Parasayu; Kurniawan Sigit Wicaksono; Mochammad Munir (Jurnal Tanah dan Sumberdaya Lahan, 2016)
The main problem in the Indonesian rubber plantations is white root rot disease (Rigidoporus microporus). White root rot disease causes the death in rubber so that the amount of crop production declines. The growth of white root rot in the soil is influenced by the nature of the soil itself that include Â soil physical, chemical and biological properties. It is known that the white root rot disease likes porous soils. The purpose of this study was to determine the effect of soil physical properties on Â the intensity of white root rot disease attacking the roots of white rubber plant. The study was done by calculating the intensity of disease and soil sampling for analysis in laboratororium. The results showed that the physical properties of soil that influenced the intensity of white root rot was organic matter 10.75%; clay fraction 30.53%; pH 30.8%; available moisture 40.69%; sand fraction 41.9% and porosity 73.37%. However, the porosity of the soil had a very strong influence and it was highly significant (p <0.01) with the regression equation y = 226.32 - 5,0311x. The high porosity of the soil was able to suppress the intensity of white root fungus attacks.